Selection of Reference Genes for Normalization of MicroRNA Expression by RT-qPCR in Sugarcane Buds under Cold Stress - Yang, Yuting; Zhang, Xu; Chen, Yun; Guo, Jinlong; Ling, Hui; Gao, Shiwu; Su, Yachun; Que, Youxiong; Xu, Liping (Frontiers in Plant Science, 2016)
Sugarcane, accounting for 80% of world’s sugar, originates in the tropics but is cultivated mainly in the subtropics. Therefore, chilling injury frequently occurs and results in serious losses. Recent studies in various plant species have established microRNAs as key elements in the post-transcriptional regulation of response to biotic and abiotic stresses including cold stress. Though its accuracy is largely influenced by the use of reference gene for normalization, quantitative PCR is undoubtedly a popular method used for identification of microRNAs. For identifying the most suitable reference genes for normalizing miRNAs expression in sugarcane under cold stress, 13 candidates among 17 were investigated using four algorithms: geNorm, NormFinder, deltaCt and Bestkeeper, and four candidates were excluded because of unsatisfactory efficiency and specificity. Verification was carried out using cold-related genes miR319 and miR393 in cold-tolerant and sensitive cultivars. The results suggested that miR171/18S rRNA and miR171/miR5059 were the best reference gene sets for normalization for miRNA RT-qPCR, followed by the single miR171 and 18S rRNA. These results can aid research on miRNA responses during sugarcane stress, and the development of sugarcane tolerant to cold stress. This study is the first report concerning the reference gene selection of miRNA RT-qPCR in sugarcane.